General Elections and the Challenges of Oligarchy in Modern Democracy - Dina M Situmeang; Rini T Simangunsong; Nasip Simbolon (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
General elections constitute a fundamental instrument of constitutional democracy, functioning as a means of realizing popular sovereignty, legitimizing political power, and ensuring political accountability. However, in the practice of modern democracy, electoral processes increasingly face serious challenges arising from the growing influence of political oligarchy, which tends to distort democratic principles. This study aims to analyze the position of general elections within the framework of constitutional democracy and to examine the impact of political oligarchy on the quality of democracy in electoral practices. The research employs a normative legal method using conceptual and statutory approaches, analyzing constitutional norms, legal doctrines, and contemporary legal and political literature. The findings indicate that general elections occupy a strategic position as a constitutional mechanism for the exercise of popular sovereignty and the peaceful circulation of power. Nevertheless, the dominance of political oligarchies, particularly through control over political parties and political-economic resources has weakened the substantive quality of democracy and undermined genuine political representation. Therefore, strengthening democracy cannot rely solely on procedural improvements in electoral systems, but must also involve systematic efforts to limit oligarchic influence and to enhance inclusive and meaningful political participation.